Dietary methionine requirement of Jing Brown layer hens from 9 to 17 weeks of age. Issue 5 (13th May 2016) - Meng, G. H.; Song, D.; Li, L. B.; Yang, C. J.; Qu, Z. X.; Gao, Y. P.
Summary: This study was conducted to evaluate the effect of dietary methionine (Met) supplementation in growth performance and reproductive performance of Jing Brown layer hens. A total of 375 9‐week‐old Jing Brown layer hens were allocated equally to five treatments consisting of 5 replicates with 15 hens. Hens were fed with a diet of corn and soya bean meal supplemented with 0.23%, 0.27%, 0.31%, 0.35% and 0.39% Met respectively. Different Met levels did not significantly affect average daily feed intake (ADFI), average daily gain (ADG) and feed/gain ratio (F/G) (p   >   0.05), whereas flock uniformity (FU) and jejunum index were significantly different (p   <   0.05), and the largest FU was observed in 0.31% Met. Dietary supplementation of Met significantly affected reproductive system development (p   <   0.05), and 0.27–0.31% Met obtained optimal reproductive system development. Different Met levels significantly affected serum uric acid and alkaline phosphatase. Moreover, the relatively higher reproductive hormones in serum were observed in 0.27% Met. Analysis of quadratic curve estimation of flock uniformity, the total number of follicles, the primary follicles and the secondary follicles showed that the optimal Met levels were 0.293%, 0.286%, 0.286% and 0.288%, which could be averaged to 0.288%. These results suggested that the optimal Met requirement for Jing Brown layer hens from 9 to 17 weeks old is 0.29%.